Involvement of heterogeneous nuclear ribonucleoproteins in viral multiplication - Castilla, Viviana (2012)
The study of virus-host interactions is a major goal in molecular virology and provides new effective targets for antiviral therapies. Heterogeneous nuclear ribonucleoproteins (hnRNPs) constitute a group of cellular RNA-binding proteins localized predominantly within the nucleus, which participate in gene transcription and subsequent RNA post-transcriptional modifications. The interaction between hnRNPs and viral components was extensively demonstrated, as well as the ability of virus infections to alter the intracellular localization or the level of expression of different hnRNPs. The involvement of these proteins in the replication of numerous viruses including members from the Retroviridae, Flaviviridae, Coronaviridae, Arenaviridae, Rhabdoviridae, Papillomaviridae, Orthomyxoviridae, Picornaviridae, Togaviridae and Herpesviridae families, has been reported. In order to gain an increased understanding of the interactions between virus and cell that result in the productive infection of the latter, in this review we discuss the main findings about the role of hnRNPs in different steps of viral replication, such as RNA synthesis, translation, RNA processing and egress of newly assembled progeny virus.